Seasonal variation, physicochemical and hydrological characteristics that influence aquatic macroinvertebrates, in a tropical river - Quesada-Alvarado, Francisco; Umaña Villalobos, Gerardo; Springer, Monika; Picado-Barboza, Jorge (Revista de Biología Tropical, 2020)
Introduction: The distribution of aquatic macroinvertebrates in rivers may be determined by the type of substrate, the shape of the river channel, the hydrological regime, and interactions with biotic and abiotic factors. Variations in the distribution of aquatic macroinvertebrates due to transitions and variations in physicochemical and hydrological characteristics are unknown in most rivers. Objectives: 1) to study the change in the aquatic macroinvertebrates assemblages in two sites in Naranjo River, during the four hydrological seasons; 2) to determine the relationship between the physicochemical variables, substrate and flow with the assemblages. Methodology: The study was conducted in the Naranjo River, Costa Rica, at two sampling sites during one year, evaluating the four seasons of the year. In each station we measure, values of water velocity and depth, flow rate, dissolved oxygen, pH, conductivity, sulfates, ammonium, nitrate, silicates, phosphates, and substrate were obtained, and a sample of aquatic macroinvertebrates was obtained for each type of microhabitat determined by water velocity. Two-way PERMANOVA was made to determine if there is a difference among aquatic macroinvertebrate abundance, per period and between sites. Canonical correspondence analysis was used to observe the relationship between aquatic macroinvertebrates and environmental factors. Finally, a Spearman’s rank correlation coefficient was performed to determine the positive or negative relationship of variables with macroinvertebrates. Results: There was a greater abundance during the dry season, while during the transition from dry to the rainy season, the lowest abundance of organisms was recorded. The CCA indicates that the first axis presented a positive relationship with the silt and sand substrate and a negative relationship for the current velocity and rock substrate variables. The second axis showed a positive relationship with flow and nitrates and negative for the pebble substrate. Most organisms showed a negative response to increased flow and nitrates. Discussion: As flow increases, current velocity increases, and not all organisms recorded in the Naranjo River have the characteristics to survive these conditions. In addition, the depth also increases along with the drag force, causing movement of smaller substrates and removal of organisms. Increased nitrates can lead to a decrease in more sensitive organisms, such as Plecoptera and Ephemeroptera. In spite of the physicochemical and flow variations registered in the Naranjo River, these were not strong enough to vary the assemblages of aquatic macroinvertebrates, so the basin does not have stressful factors that eliminate organisms during one or several months of the year.